Researching about delinquent violence in Venezuela - Moreno, Alejandro (2014)
The author, who has lived up to 30 years in Caracas’ poor neighborhoods and written many articles and books with the Popular Investigations Centre’s team (by him founded and directed), offers a brief, but complete inform about assassin violence in Venezuela. After a quick review of the main quantitative aspects, he studies in depth the qualitative dimension of this phenomenon, approaching the violent subjects’ closer motivations. Once ruled out easy causal interpretations, and detected the well founded personal/social origins of that violence, the author suggests some possible corrective interventions.